2018
DOI: 10.3390/nu10121857
|View full text |Cite
|
Sign up to set email alerts
|

Pistachio Consumption Prevents and Improves Lipid Dysmetabolism by Reducing the Lipid Metabolizing Gene Expression in Diet-Induced Obese Mice

Abstract: Pistachios contain beneficial substances such as unsaturated fatty acids, phytosterols, and polyphenols. In the present study, we investigated if pistachio consumption is able to prevent or to revert hyperglycemia, dyslipidemia, hepatic steatosis, and adipose tissue morphological alterations caused by high fat diet (HFD) in the mouse. Moreover, the impact of pistachio intake on the mRNA expression of peroxisome proliferator-activated receptor γ (PPAR-γ), fatty acid transport proteins (FAT-P), fatty acid syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 64 publications
(98 reference statements)
9
23
0
Order By: Relevance
“…The results obtained by measuring the metabolic parameters allow us to discard the supposition that the effects of pistachio consumption in the brain are a direct consequence of actions on glucose metabolism or bodyweight, because no changes in fasting glycemia, HOMA index, or body weight were observed. It was noted that the inability of chronic pistachio intake to change the bodyweight or influencing glucose dysmetabolism was already reported both in humans and animal models [15,33]. Our results suggest that the effects of regular pistachio intake are attributable to beneficial actions on lipid dysmetabolism and redox state.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The results obtained by measuring the metabolic parameters allow us to discard the supposition that the effects of pistachio consumption in the brain are a direct consequence of actions on glucose metabolism or bodyweight, because no changes in fasting glycemia, HOMA index, or body weight were observed. It was noted that the inability of chronic pistachio intake to change the bodyweight or influencing glucose dysmetabolism was already reported both in humans and animal models [15,33]. Our results suggest that the effects of regular pistachio intake are attributable to beneficial actions on lipid dysmetabolism and redox state.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, Singh et al [31] demonstrated that Pistacia vera fruit extracts improve mouse cognitive processes after chemically-induced deficits; however, the mechanisms responsible have not been clarified yet. Pistachio regular consumption has already been shown to enhance the obesity-related dysfunctions, including inflammation, by positively modulating the expression of genes linked to the lipid metabolism [4,15]. Therefore, the goal of the present study was to verify whether supplementing an HFD with pistachio fruits can mitigate the harmful effects associated with the consumption of an HFD in the brain of obese mice.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations